Comparative transcriptomic analyses of atopic dermatitis and psoriasis reveal shared neutrophilic inflammation - Choy, David F.; Hsu, Daniel K.; Seshasayee, Dhaya; Fung, Maxwell A.; Modrusan, Zora; Martin, Flavius; Liu, Fu-Tong; Arron, Joseph R. (Journal of allergy and clinical immunology, 2012)
Atopic dermatitis (AD) and psoriasis are common inflammatory diseases canonically described as involving distinct TH polarization and granulocytic infiltration. Acute AD lesions are associated with TH2 and eosinophilic inflammation, whereas psoriatic lesions are associated with TH1/TH17 and neutrophilic inflammation. Despite intensive investigation, these pathways remain incompletely understood in vivo in human subjects. Using AD and psoriatic lesional skin as exemplar TH2 and TH1/TH17 diseased tissue, we sought to clarify common and unique molecular and pathophysiologic features in inflamed skin with different types of inflammatory polarization. We conducted gene expression microarray analyses to identify distinct and commonly dysregulated expression in AD (based on Hanifin and Rajka criteria) and psoriatic lesions. We defined gene sets (GSs) as comprising genes encoding cytokines, chemokines, and growth factors that were uniquely or jointly dysregulated in patients with AD and those with psoriasis and calculated aggregate GS expression scores for lesional skin of patients with these dermatoses and healthy control skin. The atopic dermatitis gene set (AD-GS) score correlated with systemic and local measures of allergic inflammation, including serum IgE levels, blood eosinophil counts, and tissue eosinophil counts. Unexpectedly, genes encoding neutrophil chemoattractants among the common GS were highly expressed in AD lesional skin. Hematoxylin and eosin and immunohistochemical analyses showed the numbers of neutrophils in AD lesional skin were comparable with those in psoriatic lesional skin, and both were correlated with the extent of expression of neutrophil chemoattractant genes. These data are evidence that neutrophilic inflammation is a feature of lesional AD pathology comorbid with allergic inflammation.